Lettering : a reference manual of techniques - Haslam, Andrew (London : Laurence King, 2011)
Introduction/The anatomy of a letterform Chapter 1: Hand-drawn and painted lettering Calligraphy/Digital calligraphy/Graffiti/Tattooed lettering/Signwriting/Fairground painting/Canal boat painting/Road lettering and markings/Painting stained glass/Mosaic lettering Chapter 2: Typecasting, composition and design Letterpress/Hot metal composition/Book finishing/Punch-press stencils/Typewriters/Braille/Transfer lettering/Snellen eyesight test/Ishihara colour-blindness lettering/Designing type/Creating digital type Chapter 3: Printing Woodblock printing/Letterpress printing/Thermography/Lithography/Screen printing/Vitreous enamel signs/Rubber stamps/Hot foil blocking/Tin plate printing/Gravure printing/Banknotes and security printing/Dye-sublimation/Vinyl lettering/Inkjet printing/Direct to media printing Chapter 4: Cut, engraved and etched three-dimensional printing Lettercutting in wood/Lettercutting stone by hand/Lettercutting stone by machine/Sandblasting /Machine-routed letters/Hot-wire cutting/Laser cutting and etching/Pop-up and paper-cut lettering/Machine engraving/Hand engraving /Glass engraving/Acid-etching glass/Photographic etching Chapter 5: Moulded and cast three-dimensional lettering Rendered lettering/Lettering in paper /Polystyrene moulding/Vacuum-forming and thermoforming/Rapid prototyping/Coins and medals/Lettering with plants/Lettering in food/Sand casting metal/Cast-aluminium and polyurethane signs Chapter 6: Lettering in textiles Embroidery/Flag making/Machine embroidery/Cross stitch/Hand knitting/Machine knitting/Rugmaking/Woven letters Chapter 7: Illumination, animation and motion graphics Fireworks/Illuminated metal and Perspex lettering/Light boxes/Neon signs/Variable message space/Hand-drawn animation/Motion graphics: title sequences/Motion graphics: bumpers and stings Appendix/Further reading/Glossary/Index /Acknowledgements
boek